Mathematical modelling method application for catalytic reforming installation control of Achinsk oil refinery; Химия и химическая технология в XXI веке; Т. 2 - Yakupova Inna V. (Химия и химическая технология (на иностранном языке), 2014)
Заглавие с титульного экрана